Indonesian EFL students' views on using the cambly application to improve speaking skills - Hafiz, Muhammad; Daulay, Sholihatul Hamidah (Jurnal Mantik, 2025)
This study aims to evaluate the effectiveness of Cambly in improving the speaking abilities of high school students in Indonesia and to gather their perspectives on the app's usability and impact. A mixed-methods approach was used, with a sample group of 12 students who participated in one-on-one Cambly sessions over four weeks. Data was collected through pre- and post-tests measuring speaking proficiency, as well as surveys and interviews assessing user satisfaction and perceived improvements. The results indicate a significant improvement in students' speaking proficiency, with most participants reporting increased confidence and better pronunciation. However, challenges such as internet connectivity issues and subscription costs were noted. The findings suggest that Cambly can be an effective supplement to traditional English teaching methods, offering personalized and interactive language practice. Implications include the potential for schools to integrate Cambly into their language programs, with an emphasis on ensuring affordable access to digital learning tools. Future research should focus on the long-term effects of Cambly and compare its effectiveness to other language-learning platforms